A construção de cadeias referenciais em redações de português (LM) e inglês (LE) - Simas, Fábio Macedo (2009)
The present work arises from questions and inquiries about the writing process of students at high school levels, mainly in respect to the argumentative text in foreign (English) and native (Portuguese) languages. Thus, we have verified possible difficulties students might have in the construction of the referential chains (RCs) within the analysis of the referential and topic progresses and informational status in 10 compositions of students in the last year of high school. The students have been selected at a middle class´ school in São Gonçalo‐RJ. Five students have written 2 texts each: one in their native language and another in English, a foreign language, on the same subject. From these compositions, the referential strategies used by the students are listed in order to verify the referents progression, the topic progression and the informational status. Besides, data from a questionnaire, which all students have filled in, and an interview with one randomly chosen student is confronted with their texts analyses, so as to observe the students´ consciousness within the identification of the references and possible grammar errors due to the incorrect management of the RCs. The results have shown that the students are conscious of the referential strategies used in the text. Moreover, they are aware of the fact that the identification of the referents in the referential chains might contribute to detect grammar problems. The evidences have not shown relevant distinctions on the usage of the referential strategies in Portuguese and in English: in both languages, the most applied strategy was the use of the pronouns